Synthesis and Optical Properties Study of Some Metal Complexes of Poly (Vinyl Chloride)-Pyridine-4-Carbohydrazide - Abdallh, Mustafa S (Al-Nahrain Journal of Science, 2018)
Poly (vinyl chloride) (PVC) react with pyridine-4-carbohydrazide (L) in THF to form the PVC-L compound, which have been characterize by spectroscopic methods. PVC-L has further been reacted with different metals ions to form PVC-L-MII complexes. The structures of these complexes have been characterized by FTIR and UV-VIS. Spectrophotometry. The optical properties in the region from (200-900 nm) were studied using UV-VIS spectrophotometer. The optical data analyzed and interpreted in term of the theory of phonon assisted direct electronic transitions. According to energy gap data the conductivity of PVC and the complexes.